1966
DOI: 10.1021/ac60234a037
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of Titanium by Gas Chromatography.

Abstract: Because of the variety of other hydrophobic colloidal materials which are available from various companies, or which may be prepared in the laboratory, it should be possible to extend this work to permit the rapid and efficient analysis of other complex samples. It is, of course, possible to use CD-100 or other hydrophobic sols as a coating for packed columns. We performed a few tests with columns containing glass beads, or diatomaceous earth supports coated with CD-100. The resolution was not as good as with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Replacing water in eqn ( 1) and ( 2) with excess of NaOH considerably favors the forward reaction resulting in quick neutralization of the acid generating sodium chloride as shown in eqn (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing water in eqn ( 1) and ( 2) with excess of NaOH considerably favors the forward reaction resulting in quick neutralization of the acid generating sodium chloride as shown in eqn (3).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the corrosive nature of TiCl 4 routine estimation methods involving chromatography and spectroscopy are limited. [2][3][4][5] Even recent findings in this subject use highly sophisticated techniques which are far away from practical use in industries. 6,7 The estimation of TiCl 3 (OEt) and TiCl 4 in the titanation mixtures used during the catalyst preparation using reused and recovered mixed solvent assumes significance since the composition of the mixture is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy approaching 1% was obtained by Sievers ct al. (553) in the quantitative determination of titanium, as the tetrachloride, in oxide mixtures such as bauxite using a stainless steel column packed with 15% Histowax on Gas-Pack F. A homologous series of chlorosilanes with the general formula Si"-Chn+2 prepared by chlorolysis of silicon dichlorides under pressure may be separated on a column containing 20% silicon oil 550 on Celite (468). The silicon, phosphorus, and boron chlorides and bromides present in the atmosphere formed upon epitazial deposition of silicon in semiconductor processes were analyzed by GC (451).…”
Section: Physical-analyticalmentioning
confidence: 99%
“…The present authors in a previous publication (6) showed that several volatile metal fluorides can be chromatographed on a chemically conditioned poly (tetrafluoroethylene) column coated with poly (trifluoromonochloroethylene). With the exception of Sievers, Wheeler, and Ross' (12) interesting work on the determination of TiCh following reaction of Ti02 with CCh in a sealed capillary, no studies of the quantitative gas chromatographic analysis of nonvolatile inorganic compounds have yet appeared.…”
mentioning
confidence: 99%